Eredità denigrate ed eredità condivise: la teoria del romanzo in Milan Kundera e René Girard - Vignotto, Valentina (Status Quaestionis, 2024)
In Testaments Betrayed (1993), Milan Kundera’s third essay on the art of the European novel, the author describes René Girard’s Deceit, Desire, and the Novel (1961) as “the best book I have ever read on the art of the novel”. Despite some evident and seemingly irreconcilable differences in their thinking, a closer analysis of the two writers’ essays reveals a shared “anti-romantic posture”, as defined by critics, through which the relationship between novelist, literature, and the world is understood in similar and counter-current terms compared to the trends of French theory in the 1960s and 1970s. This article aims to trace the genesis of this anti-romantic alliance, starting from the rediscovery of a forgotten radio conversation between the two writers in 1989. Through this lens, the paper opens a broader analysis of three key notions: conversion, seen as a transformative experience that prevents the novelist from falling victim to the romantic postures of the “first phase” of their production; the novel as a disenchanted, clear-sighted, anti-lyrical territory where mediators, whether idols or ideals, no longer hold any allure; and literature as a tool for understanding and exploring the human condition, which is increasingly threatened by modern times.